Case of immunoglobulin G4‐related skin disease: Possible immunoglobulin G4‐related skin disease cases in cutaneous pseudolymphoma only by immunohistochemical analysis. Issue 12 (4th December 2013) - Iwata, Yohei; Mizoguchi, Yoshikazu; Takahashi, Masayuki; Tanaka, Beni; Kuroda, Makoto; Yagami, Akiko; Matsunaga, Kayoko
Abstract Immunoglobulin G4‐related disease (IgG4‐RD) is a newly recognized disease characterized by elevated serum IgG4 levels, tissue infiltration rich in IgG4+ plasma cells. We report on a case which was first considered as pseudolymphoma from the histopathological analysis, but finally diagnosed as IgG4‐related skin lesions. As the morphological features of cutaneous involvement of IgG4‐RD are consistent with those of cutaneous pseudolymphoma, we tried immunostaining past potential cases of IgG4‐RD. Thirty‐two skin specimens (15 men and 17 women; mean age, 53 years) diagnosed as having pseudolymphoma were retrieved from the archives to conduct hematoxylin–eosin, IgG and IgG4 staining. Out of the 32 cases of cutaneous pseudolymphoma, germinal center formation was seen in 22 cases, and moderate–severe fibrosis was seen in seven cases. Eleven cases showed more than 10 IgG4+ plasma cell infiltration/high‐power field, and among these 11 cases, seven cases (22%) showed A ratio of IgG4+/IgG+ cells of more than 40%. Thus, out of the 32 cases of cutaneous pseudolymphomas, two cases (6.3%) satisfied IgG4‐RD histopathological diagnostic criteria. As clinical presentations and histopathological features of skin involvement of IgG4‐RD are analogous to cutaneous B‐cell pseudolymphoma, careful identification is required through systemic examination, serum IgG4 measurement and other means.